Genotypic Investigation of Clostridium difficile in Prince Edward Island. Issue 6 (2008) - Martin, H; Abbott, LP; Low, DE; Willey, B; Mulvey, M; Weese, J Scott
Abstract : Clostridium difficile is an important cause of disease in Canada; however, little information is available about the disease in the Maritime provinces. The objective of the present study was to characterize C difficile isolates obtained from people hospitalized with C difficile infection in Prince Edward Island. One hundred twenty-six C difficile ELISA toxin-positive stool samples were obtained and cultured using an enrichment protocol. C difficile was isolated from 105 of 126 (83%) samples. Twenty-two different ribotypes were identified. The most common ribotype, ribotype W, was a North American pulsotype 2 (NAP2), toxinotype 0 strain, which represented 18% of isolates. The next most common ribotype was a NAP1, toxinotype III strain, which accounted for 11% of isolates. Ribotype 027/NAP1 only accounted for five (4.7%) isolates. Forty-five per cent of isolates possessed genes encoding production of binary toxin. Three different ribotypes, all NAP1, toxinotype III strains, had a frameshift mutation in the tcdC gene (Δ117), while one isolate (ribotype 078, NAP4, toxinotype V) had a truncating mutation (C184T) in the tcdC gene.